Examining Fraud Schemes In Village Financial Management - Puput Kurniawati; M. Nizarul Alim; Siti Musyarofah (Journal Of Social Science (JoSS), 2024)
The purpose of this study was to determine the fraud scheme that occurred in Pelangi Village from planning to accountability. This research method uses a qualitative approach. This research method is often called Naturalistic where the journey occurs naturally or in natural settings, as it is, and in normal situations, there is no manipulation of events, circumstances, and conditions so that it really matches the existing reality. The results of this study indicate that the Fraud Scheme in village financial management is indeed diverse. Fraud schemes in Pelangi Village are structured from the planning stage to the accountability stage. This organized and massive fraud scheme is not only carried out by one person but by a team or a group.